2010
DOI: 10.1159/000317023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Toll-Like Receptor 2 in Rat Diabetic Nephropathy

Abstract: Background/Aims: Inflammation is implicated in the pathogenesis of diabetic nephropathy (DN). This study examined the role of Toll-like receptor 2 (TLR2) in the progression of renal injury in a model of rat DN. Methods: DN was induced by intravenous injection of streptozotocin and rats were sacrificed at week 2, 4 and 8. Functional and pathologic markers, inflammatory infiltration, expression of TLR2, MCP-1, MyD88, HSP70, HMGB1 and activation of NF-ĸB were assessed. The effects of glucose on the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
36
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 45 publications
10
36
0
4
Order By: Relevance
“…There is an increase in the expression of TLR2 in the tubules and an upregulation of nuclear and cytoplasmic staining of HMGB1 in STZ-induced diabetic kidneys. This is consistent with the findings of Li et al (23), who demonstrate an upregulation of renal TLR2 in diabetic rats and human biopsy samples. Taken together, this suggests that TLR2 may be the integral receptor in transducing inflammation in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is an increase in the expression of TLR2 in the tubules and an upregulation of nuclear and cytoplasmic staining of HMGB1 in STZ-induced diabetic kidneys. This is consistent with the findings of Li et al (23), who demonstrate an upregulation of renal TLR2 in diabetic rats and human biopsy samples. Taken together, this suggests that TLR2 may be the integral receptor in transducing inflammation in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 93%
“…Although Lin et al did not study TLR2 expression in their diabetic in vivo model, they showed that TLR4 cortical expression in their diabetic animals was not significantly different from the wild-type controls, which is consistent with our data shown here. This is consistent with a recent study which showed prominent expression of TLR2 in the kidneys of diabetic rats with an associated increase in inflammatory infiltration (23). To date, enhanced expression of TLRs and downstream proinflammatory markers studied in in vivo models have been usually attributed to the increase in infiltrating immune cells, including the study by Devaraj et al (10), who discussed the increase in TLR2 expres- sion and its signal transduction in peritoneal and kidney macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…and micro-and macrovascular complications as well as markers of LGI and ED in patients with type 1 diabetes. The positive association between HMGB1 and albuminuria observed in this study is supported by the findings in previous studies on rats, in which higher kidney HMGB1 levels were associated with the presence and severity of diabetic nephropathy (39). In addition, it has been reported that higher HMGB1 expression was found in the cytoplasm than in the nuclei of renal tissues in diabetic rats compared with mainly nucleic HMGB1 expression in renal tissues in control rats (21).…”
Section: Discussionsupporting
confidence: 91%
“…However, they did not report on podocyte function or mesangial expansion. In contrast, Li et al (30) reported increased TLR2 expression in renal TEC in human renal biopsy DN samples as well as in kidneys of rat models of DN. However, various other reports have also provided evidence of TLR4 association in glomerular injury in DN (2,29,34).…”
Section: Discussionmentioning
confidence: 83%